Comparative study of yogic practices and dietary modifications on biochemical variables among middle-aged women on metabolic dysfunction – Associated steatotic liver disease - S. Selva Sundari; C. V. Jayanthy; S. Natarajan (International Journal of Science Annals)
Background and Aim of Study: Non-Alcoholic Fatty Liver Disease (NAFLD), now more broadly termed Metabolic Dysfunction – Associated Steatotic Liver Disease (MAFLD), poses a significant health risk for women, particularly in India where its prevalence ranges from 9.0% to 53.0%, with middle-aged women comprising 29.1% of those affected. Key risk factors include obesity, insulin resistance, metabolic syndrome, and hypertriglyceridemia reported in 95.0% of MAFLD cases. The aim of the study: to assess the effects of yoga practices, dietary modifications, and their combination on liver enzyme (ALT/SGPT), triglycerides, and fasting blood glucose levels among middle aged women with mild to moderate MAFLD. Material and Methods: Twenty-one women aged between 40 and 50 were randomly divided into three groups: yoga only (n=7), diet only (n=7), and a combination of both yoga and diet (n=7). The study was conducted for 8-week period with 6 days intervention each week. Pre- and post-test values were analysed using ANCOVA with Scheffe’s post hoc tests. Results: The study revealed that the combined Yoga and Diet intervention led to a statistically significant improvement in liver function (alanine aminotransferase, F(2,17)=15.15, p<0.05) and glycemic control (fasting glucose, F(2,17)=6.64, p<0.05) among MAFLD participants, with the Yoga+Diet group showing the greatest mean reductions (-1.43 U/L and -37.06 mg/dL respectively). While triglyceride levels also declined most in the combined group (-25.10 mg/dL), the difference was not statistically significant (F=0.41, p>0.05). Quantitative outcomes were supported by qualitative observations, including improved adherence, lifestyle engagement, and subjective well-being among participants in the combined intervention group. These findings highlight the synergistic benefits of integrating Yoga and Diet for metabolic and liver health in individuals with MAFLD. Conclusions: The study found that middle-aged women with mild to moderate MAFLD who underwent a combined yoga and dietary intervention demonstrated significant improvement in fasting blood glucose levels, indicating better glycemic control. Although reductions in alanine aminotransferase and triglyceride levels were observed across all intervention groups, these changes were not statistically significant between groups. These results suggest the combined intervention may be effective in improving metabolic health, with potential for greater impact over longer durations or in larger cohorts.